A taxonomic revision of the southern African species of the subgenus Creightonella Cockerell (Apoidea: Megachilidae: Megachile Latreille) - Eardley, Connal (Zootaxa, 2012)
The southern African species of Megachile (Creightonella) are revised. Twelve valid species are recognised, one of whichis new, Megachile serrula sp. n., and four are only known from the female. Ten new synonymies are recorded. Megachilecognata var. claripennis Friese, Megachile natalensis Friese are synonymized with Megachile cognata Smith. Megachileconsanguinea zamelaena Cockerell is synonymized with Megachile ianthoptera Smith. Megachile hopilitis Vachal,Megachile vanderysti Cockerell, Megachile triangulifera kivuicola Cockerell, and Megachile heptadonta Cockerell aresynonymized with Megachile angulata Smith. Four new lectotypes were designated; they are Megachile natalensis Friese,M. discolor Smith, M. cornigera Friese and M. braunsiana Friese. The nomenclatorial history of each species is documented, diagnoses are given, food plants are recorded and distribution maps are provided.